IKAN KOI DALAM KARYA SENI GRAFIS - Harry Suganda; Ariusmedi Ariusmedi; Irwan Irwan (Universitas Negeri Padang, 2020)
This final work aims to visualize koi fish as a reference for human behavior in the concept of creating graphic art works through acrylic media. The specialty of this koi fish is in the color, nature and behavior of koi. koi fish have a gentle nature and is a docile animal, koi fish can adapt to their new environment. In this work, one technique is stencil print. The process of creation in this work goes through several stages: the preparation, elaboration, synthesis, concept realization, and completion stages.The work created 10 pictures with the title: serenity, ambition, couple, sharing, unity, balance, mingling, generation, adaptation, faithfulness. In this final work is expected to be able to arouse the spirit of the workman in creating more interesting and unique graphic works in the future.Keywords: Koi Fish, Human Behavior, Graphic Arts